Structural design approaches for creating fat droplet and starch granule mimetics. Issue 2 (8th August 2016) - McClements, David Julian; Chung, Cheryl; Wu, Bi-cheng
Abstract : This article focuses on hydrogel-based strategies for creating reduced calorie foods with desirable physicochemical, sensory, and nutritional properties. Abstract : This article focuses on hydrogel-based strategies for creating reduced calorie foods with desirable physicochemical, sensory, and nutritional properties. Initially, the role of fat droplets and starch granules in foods is discussed, and then different methods for fabricating hydrogel beads are reviewed, including phase separation, antisolvent precipitation, injection, and emulsion template methods. Finally, the potential application of hydrogel beads as fat droplet and starch granule replacements is discussed. There is still a need for large-scale, high-throughout, and economical methods of fabricating hydrogel beads suitable for utilization within the food industry.